Preparation method and application of nickel-free and cobalt-free three-phase symbiotic sodium-electromanganese-based oxide
By doping Cu, Fe and Ti elements in manganese-based materials, a high-temperature solid phase method was used to prepare a nickel-free and cobalt-free three-phase composite structure positive electrode material, which solved the high cost and sawtooth type of nickel and cobalt elements. The problem of difficult preparation of NaMnO2 structure has achieved high specific capacity, good electrochemical performance and excellent air stability, reducing production costs.
Patent Information
- Application Number
- CN202411550150.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The high cost of nickel and cobalt in existing sodium ion batteries and the difficult-to-prepare serrated NaMnO2 structure limit the large-scale application of layered oxide positive electrode materials, while poor air stability of the materials also increases costs.
By doping Cu, Fe and Ti elements into manganese-based materials, a nickel-free and cobalt-free three-phase composite structure positive electrode material is prepared by using a simple high-temperature solid phase method, which achieves a high specific capacity of the material. Good electrochemical reversibility and excellent air stability.
This method achieves efficient preparation of nickel-free cobalt-free cathode materials, has good cycle stability, rate performance and air stability, reduces production costs, and provides strong conditions for large-scale production.
Smart Images

Figure CN119069687B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a preparation method and application of a nickel-free and cobalt-free three-phase symbiotic sodium-electric manganese-based oxide. Technical Background
[0002] Sodium-ion batteries are expected to be an effective supplement to lithium-ion batteries due to their abundant resources, low price, and similar working principles to lithium-ion batteries. Manganese-based layered transition metal oxides are a type of cathode material that is currently widely studied. NaMnO2 has two crystal forms, including a monoclinic O'3 structure (α phase) at low temperatures and an orthorhombic zigzag structure (β phase) at high temperatures. The zigzag NaMnO2 structure is strong and has a high specific capacity, but it is difficult to prepare. Therefore, how to use a simple method to prepare a layered oxide cathode material with a zigzag NaMnO2 phase is a new direction for the future development of high-performance layered oxide cathode materials.
[0003] In sodium layered oxides, nickel / cobalt elements are widely used in sodium layered oxide materials, and both play an important role in improving energy density and stabilizing crystal structure. However, due to the limited abundance of nickel and cobalt compounds in nature, the mining and processing steps are complicated, and the cost of preparing positive electrodes involving these two elements is relatively high, which hinders the large-scale application of layered oxide positive electrode materials in the field of sodium ion batteries. In addition, the Jan-Taylor effect caused by Mn3+ in layered oxides can lead to distortion of the transition metal layer structure, structural changes caused by irreversible phase changes in the deep sodium removal state, and other problems, causing rapid decay of battery capacity and shortening the battery life.
[0004] In addition, poor air stability is another key issue currently faced by layered oxides. Due to the nature of the layered structure with large sodium ions, both carbon dioxide and moisture can cause the cathode material to deteriorate, and even exposure to air for a few hours will produce alkaline residues on the surface of the material, which may cause slurry gelation, defluorination of polyvinylidene fluoride (PVDF) binder, and even corrosion of aluminum foil. Air stability requires strict control of the atmosphere during material storage, transportation and handling, which ultimately leads to a significant increase in cost.
[0005] According to previous experience, the introduction of Cu with a larger radius is conducive to the formation of β-NaMnO2 structure. At the same time, Cu doping is conducive to the weakening of Na-O bonds. This weakened Na-O bond is conducive to the cleavage of the bond during the charging process and promotes the extraction of sodium ions from the structure. In addition, the introduction of Fe with a larger radius into manganese-based materials will increase the TM-O bond length, and the band gap between the O band and the conduction band will decrease, which is conducive to better electron gain and loss of lattice oxygen. In addition, the ligand charge transfer effect of Fe 3d-O 2p can also optimize the oxygen reaction, thereby enhancing the kinetic properties of the material. However, the introduction of too much Fe will affect the cyclic stability of the material. Therefore, it is considered that the addition of Ti can alleviate the structural distortion caused by Jahn-Teller distortion and improve the cyclic stability of the material. In addition, the bond energy of Ti-O bond (666.5 KJ / mol) is higher than that of Mn-O (362 KJ / mol). Sharing oxygen with Ti can stabilize the crystal structure and inhibit the irreversible phase change caused by the slip of the transition metal layer.
[0006] Based on this, the present invention simultaneously dopes Cu, Fe, and Ti elements into manganese-based materials, and provides a method for preparing and applying a nickel-free and cobalt-free sodium positive electrode material. The material exhibits a P2 / O3 / β three-phase composite structure, retains the characteristics of high specific capacity of β-NaMnO2, and has good electrochemical reversibility, showing satisfactory cycle stability, rate performance, and excellent air stability. The present invention is synthesized by a simple solid-phase method, and no waste or exhaust gas is generated during the process, truly achieving clean and efficient production conditions. In addition, the nickel-free and cobalt-free sodium ion battery positive electrode material performs well in full battery tests and has broad prospects in large-scale production. Summary of the invention
[0007] The purpose of the present invention is to provide a nickel-free and cobalt-free sodium ion battery positive electrode material, which has the advantages of high performance and low cost, can be prepared by a simple high-temperature solid-phase method, and can be used for large-scale energy storage equipment.
[0008] Another object of the present invention is to propose a novel three-phase composite structure induced by substitution of Cu, Fe and Ti elements.
[0009] The present invention is achieved through the following technical solutions:
[0010] Sodium salt, manganese salt, copper oxide, iron oxide and titanium oxide are ground to obtain a mixture, and the mixture is calcined in an air / oxygen atmosphere and then cooled to obtain a nickel-free and cobalt-free positive electrode material.
[0011] Preferably, the molar ratio of sodium salt, manganese salt, copper oxide, iron oxide and titanium oxide is 0.9:0.65~1:0~0.2:0~0.2:0~0.2, and the sum of the molar ratios of copper oxide, iron oxide and titanium oxide does not exceed 0.35, and the composition content is any combination within this range.
[0012] Preferably, the sodium salt is derived from sodium carbonate, sodium nitrate, sodium acetate.
[0013] Preferably, the manganese salt is selected from manganese carbonate, manganese acetate, and manganese trioxide.
[0014] Preferably, the calcination is carried out at 800-1050° C. for 10-15 h, with a heating rate of 2-10° C. / min.
[0015] Compared with the prior art, the gain effect of the present invention is:
[0016] The nickel-free and cobalt-free high-specific-energy manganese-based three-phase symbiotic structure positive electrode material provided by the present invention can be prepared using a traditional solid phase reaction method, including the following steps: uniformly grinding sodium salt, manganese salt and copper, iron and titanium oxides and then simply calcining to obtain a nickel-free and cobalt-free layered oxide positive electrode material. The method does not involve a complicated and cumbersome preparation process, and the positive electrode material prepared by the method does not generate pollutants or harmful gases, and is green and clean, providing strong conditions for large-scale production.
[0017] The introduction of multiple elements of the present invention induces the formation of a novel P2 / O3 / β three-phase composite structure. The stable crystal structure and fast ion channel (through triangular prism sites) of the P2 phase enable the material to exhibit satisfactory cycle stability and rate characteristics. The characteristic peak type of the O3 phase enables the material to have a higher first-cycle charge capacity and coulombic efficiency. β-NaMnO2 is a manganese-based oxide with a zigzag structure, which provides the material with structural robustness and a relatively high specific capacity. In addition, the composite structure suppresses the slip and lattice mismatch of the transition metal layer through the interlocking effect, thereby reducing structural stress. Therefore, the present invention is superior to other comparative examples in terms of both rate performance and cycle stability.
[0018] The doping elements described in the present invention do not include expensive metal materials such as cobalt and nickel. The selected doping elements are all inexpensive and easy to obtain. The layered oxide positive electrode material prepared thereby has an obvious price advantage and is more conducive to large-scale production of the material.
[0019] In order to better meet the requirements of transportation and storage of materials in large-scale production applications, the present invention conducts an air exposure experiment on the material, and the material can still maintain a good morphology after being exposed to the air for 30 days. The electrochemical performance test shows that the capacity of the positive electrode material after being exposed to the air for 30 days is almost no decrease compared with the unexposed sample, and it has excellent rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the X-ray diffraction pattern (XRD) of the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material in Example 1.
[0021] Figure 2 This is a scanning electron microscope photograph (SEM) of the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material of Example 1.
[0022] Figure 3 This is the scanning electron microscope EDS spectrum of the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material in Example 1.
[0023] Figure 4 This is the charge and discharge curve of the first five cycles of a button cell assembled from Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material in Example 1 at a voltage range of 1.8-4.3V and a rate of 0.1C.
[0024] Figure 5 This is the charge and discharge curves of a button cell assembled from Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material in Example 1 at different rates in the voltage range of 1.8-4.3V.
[0025] Figure 6 X-ray diffraction pattern (XRD) of Na0.9Mn0.8Li0.05Fe0.1Ti0.05O2 material of comparative example 1
[0026] Figure 7 This is the charge and discharge curve of the first five cycles of a button cell assembled from Na0.9Mn0.8Li0.05Fe0.1Ti0.05O2 material in comparative example 1 at a voltage range of 1.8-4.3V and a rate of 0.1C.
[0027] Figure 8 This is the charge and discharge curves of button cells assembled from Na0.9Mn0.8Li0.05Fe0.1Ti0.05O2 materials in comparative example 1 at different rates in the voltage range of 1.8-4.3V.
[0028] Fig. 9X-ray diffraction pattern (XRD) of Na0.9Mn0.8Mg0.05Fe0.1Ti0.05O2 material of comparative example 2
[0029] Fig.10 This is the charge and discharge curve of the first five cycles of a button cell assembled from Na0.9Mn0.8Mg0.05Fe0.1Ti0.05O2 material in comparative example 2 at a voltage range of 1.8-4.3V and a rate of 0.1C.
[0030] Fig.11 Comparative Example 2: Na0.9Mn0.8Mg0.05Fe0.1Ti0.05O2 material assembled into a button cell, and the charge and discharge curves at different rates in the voltage range of 1.8-4.3V.
[0031] Fig.12 X-ray diffraction pattern (XRD) of Na0.9Mn0.8Zn0.05Fe0.1Ti0.05O2 material of comparative example 3
[0032] Fig.13 This is the charge and discharge curve of the first five cycles of a button cell assembled from Na0.9Mn0.8Zn0.05Fe0.1Ti0.05O2 material in comparative example 3 at a voltage range of 1.8-4.3V and a rate of 0.1C.
[0033] Fig.14 Comparative Example 3: Na0.9Mn0.8Zn0.05Fe0.1Ti0.05O2 material assembled into a button cell, and the charge and discharge curves at different rates in the voltage range of 1.8-4.3V.
[0034] Fig.15 X-ray diffraction pattern (XRD) of Na0.9Mn0.8Sn0.05Fe0.1Ti0.05O2 material of comparative example 4
[0035] Fig.16 This is the charge and discharge curve of the first five cycles of a button cell assembled from Na0.9Mn0.8Sn0.05Fe0.1Ti0.05O2 material in comparative example 4 at a voltage range of 1.8-4.3V and a rate of 0.1C.
[0036] Fig.17 Comparative Example 4: Na0.9Mn0.8Sn0.05Fe0.1Ti0.05O2 material assembled into a button cell, and the charge and discharge curves at different rates in the voltage range of 1.8-4.3V.
[0037] Fig.18This is a comparison chart of rate performance in the voltage range of 1.8-4.3V when Example 1 and Comparative Examples 1-4, Comparative Example 7, Comparative Example 8, and Comparative Example 11 are assembled into button cells as positive electrode materials for sodium ion batteries.
[0038] Fig.19 This is a comparison chart of the electrochemical performance of Example 1 and Comparative Examples 1-4, Comparative Example 7, Comparative Example 8, and Comparative Example 11 assembled into button cells as positive electrode materials for sodium ion batteries, and cycled 200 times at a voltage range of 1.8-4.3V and a rate of 1C.
[0039] Fig. 20 This is the in-situ XRD test result of the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material in Example 1.
[0040] Fig.21 This is the XRD comparison diagram of the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material in Example 1 after exposure for 0 days, 7 days, 15 days and 30 days.
[0041] Fig. 22 This is a scanning comparison diagram of the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material in Example 1 after exposure for 0 days, 7 days, 15 days, and 30 days.
[0042] Fig.23 This is a comparison diagram of the first-cycle charge-discharge curves of the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material in Example 1 at a voltage range of 1.8-4.3V and a current density of 0.1C after exposure for 0 days, 7 days, 15 days, and 30 days.
[0043] Fig.24 This is the first five charge and discharge curves of the full battery assembled with the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material matched with the hard carbon negative electrode in Example 1 at a current density of 0.1C.
[0044] Fig.25 This is the performance of a full battery assembled with Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material matched with a hard carbon negative electrode in Example 1 and cycled for 200 cycles. DETAILED DESCRIPTION
[0045] The present invention is further described below with reference to specific embodiments, but the present invention is not limited to the following implementation cases.
[0046] The experimental methods mentioned in the following embodiments and comparative examples are all conventional methods. The embodiments of the present invention can obtain the same results by being different from the following implementation methods. Those skilled in the art can make appropriate changes without violating the experimental results. Therefore, the present invention is not limited by the specific implementation of the following contents.
[0047] Unless otherwise specified, the reagents and materials described in the following examples can be obtained from commercial sources.
[0048] Example 1
[0049] The following is used to illustrate the preparation of a nickel-free and cobalt-free sodium ion battery positive electrode material. The material chemical formula of this embodiment is Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2.
[0050] The following is used to illustrate the preparation of nickel-free and cobalt-free sodium ion battery positive electrode materials. The preparation process is as follows:
[0051] At room temperature, the powder was weighed according to the molar ratio of sodium carbonate: manganese trioxide: copper oxide: iron trioxide: titanium dioxide of 9:8:0.5:1:0.5, and then fully ground in a natural agate mortar for 45 minutes, and then pressed into a cylindrical sheet with a thickness of about 3 mm using a mold with a diameter of 10 mm. The disc was placed in a muffle furnace, sintered to 850°C at a heating rate of 2°C / min in air, calcined for 10 hours, and naturally cooled to about 100°C to obtain a powdered positive electrode material.
[0052] The following is used to illustrate the preparation of the positive electrode sheet of a nickel-free and cobalt-free sodium-ion battery. The preparation process is as follows:
[0053] The prepared positive electrode material, polyvinylidene fluoride (PVDF) and conductive agent were mixed in a mass ratio of 7:2:1, and N-methylpyrrolidone (NMP) was added and shaken for 20 min to prepare a uniform slurry. Subsequently, the slurry was coated on the Al foil current collector and transferred to a vacuum drying oven and heated to 80 ° C for 12 h. Finally, it was cut into circular pole pieces with a diameter of 10 mm using a manual cutting machine and properly stored for later use.
[0054] The prepared positive electrode sheet is used for the preparation of sodium ion half-cell, and the preparation process is as follows:
[0055] The electrolyte uses 1 mol / L NaClO4 solvent (the solvent is a mixture of ethylene carbonate EC and dimethyl carbonate DEC in a volume ratio of 1:1, and the diaphragm (glass fiber filter paper diaphragm, Whatman GF / D, battery grade) is cut into a disc with a diameter of 20 mm. The button battery assembly uses a CR2032 button battery shell, which is assembled in the order of negative electrode shell, sodium sheet, diaphragm, positive electrode sheet, gasket, spring and positive electrode shell, and is sealed using a sealing machine at a pressure of 50MPa. The amount of electrolyte used for each button battery is about 100 microliters, and an equal amount is required to be dripped on both sides of the diaphragm to fully infiltrate the diaphragm. The entire button battery assembly process must be completed in a glove box with an argon atmosphere. In the present invention, all electrochemical performance tests are carried out at room temperature, and the voltage range of the battery test is 1.8-4.3V.
[0056] The prepared positive electrode sheet is used for the preparation of a sodium ion full battery, and the preparation process is as follows:
[0057] The electrolyte uses a self-prepared NaClO4 solvent mixture, and the diaphragm (glass fiber filter paper diaphragm, Whatman GF / D, battery grade) is cut into a disc with a diameter of 20 mm. The button battery assembly uses a CR2032 button battery shell, which is assembled in the order of the negative electrode shell, hard carbon negative electrode sheet, diaphragm, positive electrode sheet, gasket, spring and positive electrode shell, and is sealed using a sealing machine at a pressure of 50MPa. The amount of electrolyte used for each button battery is about 100 microliters, and an equal amount is required to be dripped on both sides of the diaphragm to allow the diaphragm to be fully infiltrated. The entire button battery assembly process must be completed in a glove box with an argon atmosphere. In the present invention, all full-battery electrochemical performance tests are carried out at room temperature, and the voltage range of the battery test is 1.8-4.2V.
[0058] Material structure and electrochemical performance characterization:
[0059] The crystal structure of the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 cathode material was analyzed by powder X-ray diffractometer. The results are as follows Figure 1 As shown. From the XRD diagram, it can be seen that the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material has the P2 phase, O3 phase, and β-NaMnO2 phase diffraction peaks of the layered oxide positive electrode material, while the β-NaMnO2 phase diffraction peak does not appear in each composition in the comparative example, confirming that the simultaneous doping of Cu, Fe, and Ti elements can induce the formation of a composite material with a β-NaMnO2 phase. The morphology of the finished Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 was characterized by a scanning electron microscope (DM-3100), as shown in Figure 2 As shown, the material is distributed in lamellar form. Figure 3The energy spectrum of the transmission electron microscope shows that the elements Na, Mn, Cu, Fe, Ti, and O in the material are evenly distributed in the sample particles. Figure 4 , Figure 5 The results show that the Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 material exhibits high coulombic efficiency, discharge capacity and good rate performance. It is believed that the addition of Cu and Fe provides more charge compensation for the material. At the same time, the material shows good cycle stability, and the capacity retention rate after 100 cycles at a current density of 1C is 89.7%. In order to gain a deeper understanding of the structural evolution of this example during the sodium ion insertion and extraction process, in-situ XRD tests were performed at a current density of 0.2C and a voltage range of 1.8-4.3V. Fig.19 As shown in the figure, the characteristic peak of the P2 structure returns to the initial position after the discharge, indicating that the material structure is stable, indicating that the introduction of Ti has an inhibitory effect on the Jahn-Teller effect, thereby ensuring the integrity of the material structure. The present invention was exposed to air for 30 days, and the structures exposed for 7 days, 15 days and 30 days were characterized and the electrochemical performance tested, and the results are listed in Figure 21~Figure 23 After exposure, the peak shape and morphology of the material remain intact, and the electrochemical performance is not much different, indicating that it has good air stability. The rate and cycle results of the full battery assembled with Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 and HC negative electrode are shown in the figure. Fig.24 , Fig.25 As shown, the first coulombic efficiency can reach 75%, and the capacity retention rate after 100 cycles at 0.5C reaches 88%.
[0060] Example 2
[0061] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.75Cu0.1Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0062] At room temperature, powders were weighed in a molar ratio of sodium carbonate: manganese trioxide: copper oxide: ferric oxide: titanium dioxide of 9:7.5:1:1:0.5. Other preparation conditions were the same as those in Example 1.
[0063] Example 3
[0064] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.7Cu0.15Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0065] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: copper oxide: ferric oxide: titanium dioxide of 9:7:1.5:1:0.5. Other preparation conditions were the same as those in Example 1.
[0066] Example 4
[0067] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.65Cu0.2Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0068] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: copper oxide: ferric oxide: titanium dioxide of 9:6.5:2:1:0.5. Other preparation conditions were the same as those in Example 1.
[0069] Example 5
[0070] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.83Cu0.02Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0071] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: copper oxide: ferric oxide: titanium dioxide of 9:8.3:0.2:1:0.5. Other preparation conditions were the same as those in Example 1.
[0072] Example 6
[0073] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.85Cu0.05Fe0.05Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0074] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: copper oxide: ferric oxide: titanium dioxide of 9:8.5:0.5:0.5:0.5. Other preparation conditions were the same as those in Example 1.
[0075] Example 7
[0076] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.75Cu0.05Fe0.15Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0077] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: copper oxide: ferric oxide: titanium dioxide of 9:7.5:0.5:1.5:0.5. Other preparation conditions were the same as those in Example 1.
[0078] Example 8
[0079] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.7Cu0.05Fe0.2Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0080] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: copper oxide: ferric oxide: titanium dioxide of 9:7:0.5:2:0.5. Other preparation conditions were the same as those in Example 1.
[0081] Example 9
[0082] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.75Cu0.05Fe0.1Ti0.1O2, and the specific preparation process is the same as that in Example 1, except that:
[0083] At room temperature, powders were weighed in a molar ratio of sodium carbonate: manganese trioxide: copper oxide: ferric oxide: titanium dioxide of 9:7.5:0.5:1:1. Other preparation conditions were the same as those in Example 1.
[0084] Example 10
[0085] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.7Cu0.05Fe0.1Ti0.15O2, and the specific preparation process is the same as that in Example 1, except that:
[0086] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: copper oxide: ferric oxide: titanium dioxide of 9:7:0.5:1:1.5. Other preparation conditions were the same as those in Example 1.
[0087] Embodiment 11
[0088] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.65Cu0.05Fe0.1Ti0.2O2, and the specific preparation process is the same as that in Example 1, except that:
[0089] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: copper oxide: ferric oxide: titanium dioxide of 9:6.5:0.5:1:2. Other preparation conditions were the same as those in Example 1.
[0090] Comparative Example 1
[0091] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.8Li0.05Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0092] Powders were weighed at room temperature according to the molar ratio of sodium carbonate: manganese trioxide: lithium carbonate: iron trioxide: titanium dioxide of 9:8:0.5:1:0.5, and other preparation conditions were consistent with Example 1. XRD test and electrochemical performance test were performed on the material, and the results are listed in Figure 6~Figure 8 .
[0093] Comparative Example 2
[0094] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.8Mg0.05Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0095] Powders were weighed at room temperature according to the molar ratio of sodium carbonate: manganese trioxide: magnesium oxide: iron trioxide: titanium dioxide of 9:8:0.5:1:0.5, and other preparation conditions were consistent with those in Example 1. XRD test and electrochemical performance test were performed on the material, and the results are listed in Figure 9~Figure 11 .
[0096] Comparative Example 3
[0097] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.8Zn0.05Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0098] Powders were weighed at room temperature according to the molar ratio of sodium carbonate: manganese trioxide: zinc oxide: iron trioxide: titanium dioxide of 9:8:0.5:1:0.5, and other preparation conditions were consistent with Example 1. XRD test and electrochemical performance test were performed on the material, and the results are listed in Figure 12~Figure 14 .
[0099] Comparative Example 4
[0100] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.8Sn0.05Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0101] Powders were weighed at room temperature according to the molar ratio of sodium carbonate: manganese trioxide: tin dioxide: ferric oxide: titanium dioxide of 9:8:0.5:1:0.5, and other preparation conditions were consistent with those in Example 1. XRD test and electrochemical performance test were performed on the material, and the results are listed in Figure 15~Figure 17 .
[0102] Comparative Example 5
[0103] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.8Ca0.05Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0104] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: calcium oxide: ferric oxide: titanium dioxide of 9:8:0.5:1:0.5. Other preparation conditions were the same as those in Example 1.
[0105] Comparative Example 6
[0106] The chemical formula of the material prepared in this embodiment is Na0.9Mn0.8Al0.05Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0107] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: aluminum trioxide: iron trioxide: titanium dioxide of 9:8:0.5:1:0.5. Other preparation conditions were the same as those in Example 1.
[0108] Comparative Example 7
[0109] The chemical formula of the material prepared in this comparative example is Na0.9MnO2, and the specific preparation process is the same as that in Example 1, except that:
[0110] At room temperature, powder was weighed according to a molar ratio of sodium carbonate to manganese trioxide of 9:10. Other preparation conditions were the same as those in Example 1.
[0111] Comparative Example 8
[0112] The chemical formula of the material prepared in this comparative example is Na0.9Mn0.95Fe0.05O2, and the specific preparation process is the same as that of Example 1, except that:
[0113] At room temperature, powders were weighed in a molar ratio of sodium carbonate: manganese trioxide: ferric oxide of 9:9.5:0.5. Other preparation conditions were the same as those in Example 1.
[0114] Comparative Example 9
[0115] The chemical formula of the material prepared in this comparative example is Na0.9Mn0.9Fe0.1O2, and the specific preparation process is the same as that in Example 1, except that:
[0116] At room temperature, powders were weighed in a molar ratio of sodium carbonate: manganese trioxide: ferric oxide of 9:9:1. Other preparation conditions were the same as those in Example 1.
[0117] Comparative Example 10
[0118] The chemical formula of the material prepared in this comparative example is Na0.9Mn0.85Fe0.15O2, and the specific preparation process is the same as that of Example 1, except that:
[0119] At room temperature, powders were weighed in a molar ratio of sodium carbonate: manganese trioxide: ferric oxide of 9:8.5:1.5. Other preparation conditions were the same as those in Example 1.
[0120] Comparative Example 11
[0121] The chemical formula of the material prepared in this comparative example is Na0.9Mn0.95Ti0.05O2, and the specific preparation process is the same as that of Example 1, except that:
[0122] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: titanium dioxide of 9:9.5:0.5. Other preparation conditions were consistent with those in Example 1.
[0123] Comparative Example 12
[0124] The chemical formula of the material prepared in this comparative example is Na0.9Mn0.9Ti0.1O2, and the specific preparation process is the same as that of Example 1, except that:
[0125] At room temperature, powders were weighed in a molar ratio of sodium carbonate: manganese trioxide: titanium dioxide of 9:9:1. Other preparation conditions were the same as those in Example 1.
[0126] Comparative Example 13
[0127] The chemical formula of the material prepared in this comparative example is Na0.9Mn0.85Ti0.15O2, and the specific preparation process is the same as that of Example 1, except that:
[0128] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: titanium dioxide of 9:8.5:1.5. Other preparation conditions were consistent with those in Example 1.
[0129] Comparative Example 14
[0130] The chemical formula of the material prepared in this comparative example is Na0.9Mn0.85Fe0.1Ti0.05O2, and the specific preparation process is the same as that in Example 1, except that:
[0131] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: ferric oxide: titanium dioxide of 9:8.5:1:0.5. Other preparation conditions were consistent with those in Example 1.
[0132] Comparative Example 15
[0133] The chemical formula of the material prepared in this comparative example is Na0.9Mn0.9Cu0.05Ti0.05O2, and the specific preparation process is the same as that of Example 1, except that:
[0134] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: copper oxide: titanium dioxide of 9:9:0.5:0.5. Other preparation conditions were the same as those in Example 1.
[0135] Comparative Example 16
[0136] The chemical formula of the material prepared in this comparative example is Na0.9Mn0.85Fe0.1Cu0.05O2, and the specific preparation process is the same as that of Example 1, except that:
[0137] At room temperature, powders were weighed according to a molar ratio of sodium carbonate: manganese trioxide: ferric oxide: copper oxide of 9:8.5:1:0.5. Other preparation conditions were the same as those in Example 1.
[0138] The basic electrochemical properties of each embodiment and comparative example are listed in Table 1.
[0139] Table 1 Electrochemical performance data of each embodiment and comparison
[0140] Cathode Materials First cycle charge capacity (mAh g-1) First coil discharge specific capacity (mAh g-1) Capacity retention rate 100 cycles@1C (%) Example 1 Na0.9Mn0.8Cu0.05Fe0.1Ti0.05O2 158 158 89.7 Example 2 Na0.9Mn0.75Cu0.1Fe0.1Ti0.05O2 155 152 77.5 Example 3 Na0.9Mn0.7Cu0.15Fe0.1Ti0.05O2 143 135 90.2 Example 4 Na0.9Mn0.65Cu0.2Fe0.1Ti0.05O2 124 115 87.5 Example 5 Na0.9Mn0.83Cu0.02Fe0.1Ti0.05O2 158 155 81.1 Example 6 Na0.9Mn0.85Cu0.05Fe0.05Ti0.05O2 155 157 83.3 Example 7 Na0.9Mn0.75Cu0.05Fe0.15Ti0.05O2 156 158 82.1 Example 8 Na0.9Mn0.7Cu0.05Fe0.2Ti0.05O2 155 153 78.2 Example 9 Na0.9Mn0.75Cu0.05Fe0.1Ti0.1O2 138 140 81.2 Example 10 Na0.9Mn0.7Cu0.05Fe0.1Ti0.15O2 139 132 75.2 Embodiment 11 Na0.9Mn0.65Cu0.05Fe0.1Ti0.2O2 135 128 76.6 Comparative Example 1 Na0.9Mn0.8Li0.05Fe0.1Ti0.05O2 163 146 65.1 Comparative Example 2 Na0.9Mn0.8Mg0.05Fe0.1Ti0.05O2 140 144 55.1 Comparative Example 3 Na0.9Mn0.8Zn0.05Fe0.1Ti0.05O2 134 133 71.4 Comparative Example 4 Na0.9Mn0.8Sn0.05Fe0.1Ti0.05O2 130 137 60.3 Comparative Example 5 Na0.9Mn0.8Ca0.05Fe0.1Ti0.05O2 120 118 70.1 Comparative Example 6 Na0.9Mn0.8Al0.05Fe0.1Ti0.05O2 112 110 62.1 Comparative Example 7 Na0.9MnO2 154 150 53.6 Comparative Example 8 Na0.9Mn0.95Fe0.05O2 149 137 48.4 Comparative Example 9 Na0.9Mn0.9Fe0.1O2 145 140 32.8 Comparative Example 10 Na0.9Mn0.85Fe0.15O2 134 125 34.5 Comparative Example 11 Na0.9Mn0.95Ti0.05O2 137 132 50.8 Comparative Example 12 Na0.9Mn0.9Ti0.1O2 130 125 58.1 Comparative Example 13 Na0.9Mn0.85Ti0.15O2 123 120 65.2 Comparative Example 14 Na0.9Mn0.85Fe0.1Ti0.05O2 144 147 66.7 Comparative Example 15 Na0.9Mn0.9Cu0.05Ti0.05O2 131 138 50.1 Comparative Example 16 Na0.9Mn0.85Fe0.1Cu0.05O2 120 124 45.4
Claims
1. A nickel-free and cobalt-free three-phase symbiotic sodium ion battery manganese-based oxide positive electrode material, characterized in that: The positive electrode material is a P2 / O3 / β phase three-phase composite structure with a chemical formula of Na x Mn y Cu z Fe m Ti n O2, 0.8≤x≤1, y+z+m+n=1, 0.65≤y≤1, 0 <z<0.2,0<m<0.2,0<n<0.2。 2. A method for preparing a nickel-free and cobalt-free three-phase symbiotic sodium ion battery manganese-based oxide positive electrode material according to claim 1, characterized in that: The method comprises the following steps: grinding sodium salt, manganese salt, copper oxide, iron oxide and titanium oxide to obtain a mixture, calcining the mixture and then cooling it to obtain a nickel-free and cobalt-free positive electrode material, wherein the molar ratio of the sodium salt, manganese salt, copper oxide, iron oxide and titanium oxide is 0.9:0.65-1:0-0.2:0-0.2:0-0.2, and the sum of the molar ratios of the copper oxide, the iron oxide and the titanium oxide does not exceed 0.35, the sodium salt comes from one of sodium carbonate, sodium nitrate and sodium acetate, the manganese salt comes from one of manganese carbonate, manganese acetate and manganese trioxide, the sintering atmosphere is air or oxygen atmosphere, the sintering equipment is a muffle furnace, the sintering temperature is 800-1050°C, and the heating rate is 2-10°C / min.
3. A sodium ion battery based on a nickel-free and cobalt-free three-phase symbiotic manganese-based oxide positive electrode material, characterized in that: The invention comprises the manganese-based oxide positive electrode material as claimed in claim 1.